Biopreservantes contra el manchado azul de la madera de pino caribe - Briceño, A.=700 1 Encinas, O.; Mohali, S.; Mora, N.; Molina, Y.
(Es, En)
Ilus., 21 ref.
Keywords: PINUS CARIBAEA; CONTROL BIOLOGICO; CONSERVANTES DE LA MADERA; TRICHODERMA HARZIANUM; ASPERGILLUS; DAÑOS; HONGOS; SPHAEROPSIS; VENEZUELA; PINUS HONDURENSIS; MANCHADO AZUL; REVISTA FORESTAL VENEZOLANA